Myeloid-Derived Suppressor Cells in Bacterial Infections - Ost, Michael; Singh, Anurag; Peschel, Andreas; Mehling, Roman; Rieber, Nikolaus; Hartl, Dominik (Frontiers in Cellular and Infection Microbiology, 2016)
Myeloid-derived suppressor cells (MDSCs) comprise monocytic and granulocytic innate immune cells with the capability of suppressing T- and NK-cell responses. While the role of MDSCs has been studied in depth in malignant diseases, the understanding of their regulation and function in infectious disease conditions has just begun to evolve. Here we summarize and discuss the current view how MDSCs participate in bacterial infections and how this knowledge could be exploited for potential future therapeutics.